Effect of hydroquinone on electrochemical oxidation of polypyrrole - Kim, DY; Choi, JH; Kim, SH; Cho, HN; Kim, CY (ELSEVIER SCIENCE SA LAUSANNE, 1997)
Polypyrrole(PPy) formed electrochemically lost the redox reactivity with repeated cycles. The reactivity was preserved greatly by adding 0.005M of hydroquinone in the system. The improved stability of PPy in redox reaction may be attributed to the stabilization of free radicals in the polaron structure by hydroquinone.